Blockchain web-based e-voting system for UMS student council - Stanley Paul David (2022)
In the current status quo there are many innovations that are being brought forward to existing systems. These innovations help to provide a better functioning application. One particularly emerging field in innovation are blockchains. Blockchain technology offers an array of benefits from the field of economics to data storage. A blockchain is a data storage method that connects blocks with a chain. The blocks data cannot be modified once it has been stored as a block. The blockchain application in e-voting provides a open, fair and immutable. By storing the votes onto the blockchain the data is then safe and unmodifiable. Current systems use a database to store the votes. This paper proposes a system for e-voting that incorporates a blockchain as the main method for storing votes. This system is designed to fulfill the requirements of a democratic voting system and offers a degree of decentralization. The objective of this paper is to investigate and research blockchain security features, design and develop the proposed blockchain based e-voting system and evaluate the security that this system provides. The blockchain is built using Python programming language. A waterfall methodology approach is used to develop, analyze, and design the proposed system. Implementation of the system was done locally using XAMPP and testing was done locally. To conclude, this paper has shown that it is a viable alternative to traditional e-voting systems.